The Distinction Between State and Government. Issue 8 (2nd August 2013) - Robinson, Edward Heath
Abstract: The terms "state" and "government" are often used interchangeably in political discourse, but they can also refer to very different entities. In political geography, a distinction between the two is often not made, or made weakly. Thus, this article reviews how these terms have been used in political geography and across allied disciplines, especially in international law. Political geographers commonly seem to draw from the anthropological and sociological uses of the terms, but the distinction between state and government is arguably most developed in international legal scholarship. This article argues that political geography would gain by adopting a distinction between state and government as it is articulated in international legal scholarship. Drawing from that literature, this article recommends that states be contrasted with governments in the following way: states are juridical entities of the international legal system; governments are the exclusive legally coercive organizations for making and enforcing certain group decisions. Arguably, ambiguity regarding the referents of these terms has hindered the development of state theory and even made it unclear what the "theory of the state" is supposed to explain. Therefore, this article concludes with a call for geographers to be just as cognizant of the distinction between state and government as they traditionally have been of the distinction between state and nation.